Men, Masculinities and Intimate Partner Violence (Routledge Research in Gender and Society, 2021)
Men, Masculinities and Intimate Partner Violence examines how gender and other social identities and inequalities shape experiences of, and responses to, violence in intimate relationships. It provides new insights into men as both perpetrators and victims of violence, as well as on how to involve men and boys in anti-violence work. The chapters explore partner violence from the perspectives of researchers, therapists, activists, organisations, media as well as men of different background and sexual orientation. Highlighting the distinct and ambivalent ways we relate to violence and masculinity, this timely volume provides nuanced approaches to men, masculinity and intimate partner violence in various societies in the global North and South. This book foregrounds scholarship on men and masculinities in the context of intimate partner violence. By doing so, it revitalises feminist theorising and research on partner abuse, and brings together the fields of masculinity studies and studies of intimate partner violence. The book will be a vital resource for students and scholars in criminology, gender studies, psychology, social work and sociology, as well as those working with men and boys.